2009
DOI: 10.1089/ham.2008.1103
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Responses in Young Adults First Exposed to High Altitude for 12 Months at 3550 m

Abstract: To determine the changes in blood pressure (BP) and related variables in sea-level young adults with chronic exposure to high altitude, a longitudinal study was performed in male army recruits (n = 346; age 17.9 +/- 0.1 yr; BMI, 22.5 +/- 0.3 kg/m(2)) first exposed to 3550-m altitude for 12 months. Fifty male recruits (age 17.8 +/- 0.6 and BMI 22.6 +/- 0.3 kg/m(2)) never exposed to altitude were used as controls. A sustained higher mean diastolic BP (DBP) (82.1 +/- 1.0 mmHg at month 3; 81.3 +/- 0.9 mmHg at mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
3
36
2
1
Order By: Relevance
“…However, in one study [21], both SBP and DBP reduced after hypoxic training, 26mmHg and 8mmHg respectively, while increases in SBP and DBP were reported another study [22]. Chronic exposure to hypoxic training for ≥ three weeks resulted in mixed findings, with one study reporting reductions in SBP and DBP (p<0.05) [6] two studies [23,24] reporting increase in both SBP and DBP, and no change in one study [9]. Higher levels of altitude ≥ 4000m increased both SBP and DBP [22][23][24], while at moderate levels of altitude (1,700m-2,740m), blood pressure levels either maintained or improved [6,7,9,19,21].…”
Section: Blood Pressurementioning
confidence: 98%
See 3 more Smart Citations
“…However, in one study [21], both SBP and DBP reduced after hypoxic training, 26mmHg and 8mmHg respectively, while increases in SBP and DBP were reported another study [22]. Chronic exposure to hypoxic training for ≥ three weeks resulted in mixed findings, with one study reporting reductions in SBP and DBP (p<0.05) [6] two studies [23,24] reporting increase in both SBP and DBP, and no change in one study [9]. Higher levels of altitude ≥ 4000m increased both SBP and DBP [22][23][24], while at moderate levels of altitude (1,700m-2,740m), blood pressure levels either maintained or improved [6,7,9,19,21].…”
Section: Blood Pressurementioning
confidence: 98%
“…Higher levels of altitude ≥ 4000m increased both SBP and DBP [22][23][24], while at moderate levels of altitude (1,700m-2,740m), blood pressure levels either maintained or improved [6,7,9,19,21]. Although improvements in SBP and DBP were not evident in healthy subjects [9,[18][19][20][22][23][24][25], patients diagnosed with hypertension resulted in 8-13mmHg [6,7,21] reduction in DBP and up to 26mmHg [21] reduction in SBP at altitudes of 1,285m-2,650m [6,7,21]. With patients with obesity (BMI ≥30kg/m 2 ), one week of exposure to altitude of 2650m resulted in DBP reduction of 13.9% [7], however ,no change in blood pressure were observed with non-hypertensive patients with obesity [9].…”
Section: Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…found AMS in almost 60% of the population. Three months later when soldiers descended to the lowland for over a week and re-ascended, the symptoms of AMS were noted in 55% [27]. Still another study in tourists climbing Kilimanjaro the symptoms of acute mountain sickness were observed in 9% of participants at the altitude of 2743 m a.s.l.…”
Section: Incidence Of Amsmentioning
confidence: 92%